Pendekatan dan Model Pembelajaran Kurikulum 2013 - Fanani, Moh. Zaenal (Didaktika Religia, 2013)
The article discusses the characteristics of the 2013 curriculum and how it differs from the previous ones. The development of learning methodologies becomes one of the reasons for structuring educational curriculum in Indonesia, i.e. curriculum 2013. Aspects of changes in the Curriculum 2013 compared to the previous curriculum in terms of teaching methodology are Scientific Learning Approach, Discovery Learning model, Problem-Based Learning Model, and Project-Based Learning Model. This new curriculum can be classifiend into Constructivism which strengthened the previous learning theory and enlightened the transformation of teacher-centered learning approach towards the concept of student-centered learning approach. The later results in severalÂ  approaches and methods of active learning.